Optimal Orbit Transfer Under Earth Zonal Potential - In-Sang Moon; Jong-Uk Park; Young-Soo Seoh; Kyu-Hong Choi (Journal of Astronomy and Space Sciences, 1990)
It was investigated that the effect of zonal harmonics to transfer orbit. Since parking orbit is located at low altitude, the zonal harmonics affects transfer orbit relatively high sense. So under the zonal harmonics, eccentricity and semi-major-axis which were related orbit altitude au the first hand, were investigated. As a result the zonal harmonics increases the altitude of apogee of transfer orbit. So if the zonal harmonics is considered in orbit transfer the fuel can be saved a little.